Analysis of SNR of Physical Layer of 802.16e WiMAX under AWGN Channel and Doppler impact for Rician Blurring Channel with various Digital Modulation Techniques - Santosh Pawar, Mahesh Pasari (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The drive to provide high-speed, cost-effective, and broadly accessible broadband wireless access (BWA) technologies has been a cornerstone in the evolution of the 802.16 standards, known as WiMAX. This standard outlines the air interface specifications for fixed BWA systems, operating within the 10-66 GHz frequency range. A significant body of research, including the model discussed in this context, has been devoted to evaluating the performance of the WiMAX Physical Layer (PHY) across various channel conditions, employing different digital modulation techniques. This analytical approach specifically focuses on measuring the system’s efficacy by observing the impact on packet and bit loss rates under the IEEE 802.16 standard. Through such in-depth analysis, the model aims to shed light on the potential and limitations of WiMAX technology in delivering robust and efficient wireless broadband services.